A novel molecular mechanism to explain mutations of the HCV protease associated with resistance against covalently bound inhibitors - Nazario de Moraes, Leonardo [UNESP]; Tommasini Grotto, Rejane Maria [UNESP]; Targino Valente, Guilherme [UNESP]; de Carvalho Sampaio, Heloisa [UNESP]; Magro, Angelo José [UNESP]; Fogaça, Lauana [UNESP]; Wolf, Ivan Rodrigo [UNESP]; Perahia, David; Faria Silva, Giovanni [UNESP]; Plana Simões, Rafael [UNESP] (Elsevier, 2019)
NS3 is an important therapeutic target for direct-acting antiviral (DAA) drugs. However, many patients treated with DAAs have unsustained virologic response (UVR) due to the high mutation rate of HCV. The aim of this work was to shed some light on the puzzling molecular mechanisms of the virus's of patients who showed high viral loads even under treatment with DAA. Bioinformatics tools, molecular modelling analyses were employed to identify mutations associated with HCV resistance to boceprevir and possible structural features related to this phenomenon. We identified two mutations of NS3 that may be associated with HCV resistance: D168N and L153I. The substitution D168N was previously reported in the literature as related with drug failure. Additionally, we identified that its molecular resistance mechanism can be explained by the destabilization of receptor-ligand hydrogen bonds. For the L153I mutation, the resistance mechanism is different from previous models reported in the literature. The L153I substitution decreases the S139 deprotonation susceptibility, and consequently, this mutation impairs the covalent binding between the residue S139 from NS3 and the electrophilic trap on boceprevir, which can induce drug failure. These results were supported by the time course analysis of the mutations of the NS3 protease, which showed that boceprevir was designed for enzymes with an L residue at position 153; however, the sequences with I153 are predominant nowadays. The results presented here could be used to infer about resistance in others DAA, mainly protease inhibitors.
Keywords: Boceprevir; Direct-acting antiviral; HCV; Resistance associated substitutions; Treatment failure